Carotid transient ischemic attacks presenting as limb-shaking syndrome: report of two cases - Pedro A. Kowacs; André R. Troiano; Célio Teixeira Mendonça; Hélio A.G. Teive; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
Limb shaking syndrome (LSS) is a rare presentation of transient ischemic attacks (TIAs), usually secondary to a critical carotid stenosis compromising intracranial circulation, first described 40 years ago. Two additional cases are described herein, aiming to add on to previous descriptions, and to warn physicians about this potentially harming and rather uncommon condition.